OPHIOLITE INHERITANCE IN THE PO PLAIN SEDIMENTS: INSIGHTS ON HEAVY METALS DISTRIBUTION AND RISK ASSESSMENT - Bianchini, Gianluca; Di Giuseppe, Dario; Natali, Claudio; Beccaluva, Luigi (Ofioliti, 2013)
High heavy metals backgrounds, in particular chromium and nickel, are renowned in soils and sediments of the Po Plain. New XRF data, synthetized in geo-referenced geochemical maps, emphasize that the anomalously high Cr-Ni backgrounds are related to the fine alluvial sediments of the Po River. A com- parison with the regolith composition of ophiolite rocks cropping out within the Po River basin suggests that the observed geochemical features reflect sedi- mentary components deriving from the weathering of femic and ultrafemic rocks. The elevated Cr-Ni backgrounds are therefore a geogenic character of the Po River alluvial sediments, unrelated to anthropogenic contamination. Electron microprobe investigation focused on femic minerals highlights that nickel is mainly sequestrated in serpentine (up to 0.4 wt%) whereas chromium is mainly hosted in chlorite (up to 2.5 wt%). Extraction tests, in which leachates have been analysed by ICP-MS, reveal that the mobility of chromium is limited; coherently the natural water of the area usually display concentration lower than the national drinking standards. Unfortunately, this element is considered toxic and dangerous even at extremely low concentration if oxidized in the hexava- lent form that is prevalent in supergene conditions, thus posing serious environmental concerns. Nickel, on the other hand, displays a higher mobility, possibly due to the metastable behaviour of serpentine. Coherently the Cr/Ni is always higher than one in the investigated sediments and soils, whereas is always lower than one in both the natural waters and agricultural products of the area. Therefore, the high nickel concentration represents further geochemical risk and the relative content has to be monitored in the local agricultural crops. For the same reasons, aquaculture activities such as mussels and clam farms developed in the lagoons widespread around the delta of Po River are also potentially exposed to nickel bio-accumulation and the related products have to be carefully monitored.